Nurses' Perceptions of Pediatric Palliative Care with Cancer In Hospitals In Bandung City - Abas, Latifa Hidayani; Mediani, Henny Suzana; Agustina, Hana Rizmadewi (IJNP (Indonesian Journal of Nursing Practices), 2024)
Background: Pediatric palliative care (PPC) has seen significant progress in recent decades. Despite the improvements in care, nurses still feel anxious, fearful, and hesitant in providing PPC. More research efforts are needed to identify and explore nurses' perceptions of PPC in children with cancer.Objective: The aim of this study was to explore nurses' perceptions of palliative care in children with cancer.Methods: This study was a descriptive qualitative study. Participants were selected using purposive sampling. They were eleven nurses from Kenanga Room 2 of Hasan Sadikin Hospital, Bandung. Data were collected using semi-structured interviews and analyzed using thematic analysis method. The research was conducted from March to April 2023.Results: This study identified four main themes and nineteen subthemes. The themes in this study are (1) Nurses' understanding of PPC, (2) Barriers to the implementation of PPC in children with cancer (3) Nurses' needs and expectations for PPC improvement, and (4) Roles and responsibilities of nurses in PPC.Conclusions: This study described the clinical reality of nurses providing PPC to children with cancer in one of the hospitals in Indonesia. The findings suggested that addressing these challenges could lead to significant improvements in pediatric palliative care practices in the hospital setting.